ANALISIS EFISIENSI BIAYA TENAGA KERJA LANGSUNG PADA PT. ADINATA SUNGGUMINASA - Andi Rustam; Andi arifwangsa; Adiningrat Adiningrat (Universitas Muhammadiyah Makassar, 2019)
Research is done with the aim of to know the cost-efficient direct manpower undertaken by the company PT. Adinata.. In this study, the literature and observations review was by conducting research on the field through live interviews and data retrieval, related documents from the company as well as the use of books, and internet media. The Data obtained in the analysis using quantitative analysis method is how to compare between real labor cost (Actual) with budgeted, which often happens deviation from budget called Variance. The results showed that based on the analysis observation that researchers have done showed that the efficiency rate of labor cost at PT. Adinata in a time span of 2014-2016 is 10.5586%. It shows that direct energy cost control is in the category of efficient and stable.